Electroencephalographic Findings in Patients with Migraine - Mishra, Tapaswini; Mohapatra, Dipti; Panda, Priyambada; Meher , Arati; Devi, Ellora (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Migraine is a common, debilitating disorder that imposes a large personal burden on sufferers and high economic costs on society. Sufferers have a significant level of migraine-related disability in all aspects of their daily lives, including employment, household work, and non-work activities. Since there is a wide range of disorders that cause headaches, a systematic approach to classification and diagnosis is an essential prelude to clinical management and to useful research. The Electroencephalogram (EEG) is frequently used in the examination of patients with migraine nowadays. High voltage abnormal slow-wave activity is seen in some patients with migraine. Several types of abnormal EEG were reported in basilar migraine including 1) an excess beta activity in the ictal phase in children 2) predominant delta activity during the attack of headache and normal EEG during attack 3) slowing in the posterior region or slowing with spikes and sharp wave complexes 54-56 and 4) unusual association of acute confusional state with FIRDA (frontal intermittent rhythmic delta activity) during the attack of migraine.